Help in the Classroom - Balshaw, Margaret H. (London : David Fulton, 1999)
This largely rewritten 2nd edition comprises an overview of the latest developments in research, legislation and practice with regard to the support, management and staff development needs of learning support assistants in mainstream and special schools.
Previous ed.: 1991.
Includes bibliographical references (p. 120).
Keywords: Teachers' assistants; Special education; Education